The Role of Proton Transfer on Mutations - Srivastava, Ruby (Frontiers in Chemistry, 2019)
Hydrogen bond plays a critical role in DNA and RNA studies as it encodes genes and maps protein structures. These bonds provide stability to the base pairs and involved in the spontaneous and induced mutations. Covalent and non-covalent interactions offer a powerful tool for the development of advanced functional materials with potential applications for medical and molecular sciences. As the mechanisms of untargeted mutations are poorly understood, so in this mini-review, the analysis will be focused on the canonical, wobble, Hoogsteen pairs, and mutagenic tautomers through the non-covalent interactions. Further rare tautomers formation through the single proton transfer (SPT) and the double proton transfer (DPT), quantum tunnelling in DNA, radiation-induced bystander effects, role of water in PT reactions, PT in anticancer drugs-DNA interaction, displacement and oriental polarization, simultaneous double proton-transfer (SDPT) mechanism adapted for gold surface, possible models for the mutations in DNA, genome instability, role of proton transfer using kinetic parameters, concerted-double proton transfer, step-wise mechanism for RNA will be discussed.